2016
DOI: 10.1007/s00449-016-1716-4
|View full text |Cite
|
Sign up to set email alerts
|

Cellulase immobilization on magnetic nanoparticles encapsulated in polymer nanospheres

Abstract: Immobilization of cellulases on magnetic nanoparticles, especially magnetite nanoparticles, has been the main approach studied to make this enzyme, economically and industrially, more attractive. However, magnetite nanoparticles tend to agglomerate, are very reactive and easily oxidized in air, which has strong impact on their useful life. Thus, it is very important to provide proper surface coating to avoid the mentioned problems. This study aimed to investigate the immobilization of cellulase on magnetic nan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
18
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 58 publications
(19 citation statements)
references
References 27 publications
0
18
0
1
Order By: Relevance
“…Nevertheless, the results clearly show that immobilization is an effective tool to ensure the reusability of cellulase in the hydrolysis of cellulose. Earlier studies of cellulase immobilization have reported the retention of about 40% and 70% of initial activity after eight biocatalytic cycles, when the enzyme was attached to, respectively, magnetic nanoparticles consisting of hematite and ferrite activated by glutaraldehyde, and magnetic nanoparticles encapsulated in polymer nanospheres [34,42]. Such improvement in the operational stability and reusability of cellulase makes it more suitable for large-scale processes and greatly increases its economic viability.…”
Section: Stability Study Of Immobilized Cellulasementioning
confidence: 99%
“…Nevertheless, the results clearly show that immobilization is an effective tool to ensure the reusability of cellulase in the hydrolysis of cellulose. Earlier studies of cellulase immobilization have reported the retention of about 40% and 70% of initial activity after eight biocatalytic cycles, when the enzyme was attached to, respectively, magnetic nanoparticles consisting of hematite and ferrite activated by glutaraldehyde, and magnetic nanoparticles encapsulated in polymer nanospheres [34,42]. Such improvement in the operational stability and reusability of cellulase makes it more suitable for large-scale processes and greatly increases its economic viability.…”
Section: Stability Study Of Immobilized Cellulasementioning
confidence: 99%
“…Lima et al found that immobilized cellulase had increased thermostability when compared to free cellulase and retained nearly 70% of its initial activity after eight cycles of converting cellulosic biomass to glucose. The significant activity retention of immobilized cellulose suggests that immobilization techniques can improve process economics by allowing for efficient reuse of biocatalyst [56].…”
Section: The Food-water-fuel Nexusmentioning
confidence: 99%
“…Enzyme stability and activity were affected by the immobilization process as detailed in Table 4. The results obtained revealed that poly(methyl methacrylate) as a coating polymer did not have any significant effect on the particles' magnetic properties (Figure 4) [70]. Four-arm dendritic polymers composed of PEG-NH2 (Scheme 5) were used as coating materials for immobilization of cellulase derived from Trichoderma viride onto MNPs.…”
Section: Cellulase Immobilization On Composite-functionalized Mnpsmentioning
confidence: 99%
“…Providing unique physical and electronic properties and also providing a large surface area for biomolecules to anchor [69][70][71][72] Amino-based surface functionalization Novel strategies to enhance the enzyme's thermal and chemical stability [63][64][65][66][67] Chitosan-based surface functionalization…”
Section: Silica-based Surface Functionalizationmentioning
confidence: 99%
See 1 more Smart Citation